Effects of structural changes of new organophosphorus cationic exchangers on a solvent extraction of cobalt, nickel and manganese from acidic chloride media. Issue 10 (17th January 2017) - Omelchuk, Kateryna; Szczepański, Piotr; Shrotre, Akhilesh; Haddad, Mansour; Chagnes, Alexandre
Abstract : The effects of structural changes of organophosphorus cationic exchangers on metal-distribution curves (extraction efficiency vs. pH) have been investigated for the recovery of cobalt(ii ), nickel(ii ) and manganese(ii ) from acidic chloride solutions. Abstract : The effects of structural changes of organophosphorus cationic exchangers on metal-distribution curves (extraction efficiency vs. pH) have been investigated for the recovery of cobalt(ii ), nickel(ii ) and manganese(ii ) from acidic chloride solutions. By using alkyl groups with different branching and hydrophobicity and by including oxygen atoms in the hydrophobic chains of the cationic exchangers, it has been shown that the change of the chemical structure in the hydrophobic chains plays an important role in the extraction behaviours and causes more specifically a shift of the extraction curves to higher or lower pH depending on p K a values of extracting agents (evaluated by using QSPR calculations), distribution constants of metal–ligand complexes between organic and aqueous phases and the formation constant of the metal–ligand complexes. Based on the present results, interest in the new cationic exchangers synthesized in the present work for cobalt(ii ), nickel(ii ) and manganese(ii ) separation is also discussed.